Surgical Release of the Pectoralis Minor Tendon for Scapular Dyskinesia and Shoulder Pain. (January 2017) - Provencher, Matthew T.; Kirby, Hannah; McDonald, Lucas S.; Golijanin, Petar; Gross, Daniel; Campbell, Kevin J.; LeClere, Lance; Sanchez, George; Anthony, Shawn; Romeo, Anthony A.
Background: Pectoralis minor (PM) tightness has been linked to pain and dysfunction of the shoulder joint secondary to anterior tilt and internal rotation of the scapula, thus causing secondary impingement of the subacromial space. Purpose: To describe outcomes pertaining to nonoperative and operative treatment via surgical release of the PM tendon for pathologic PM tightness in an active population. Study Design: Case series; Level of evidence, 4. Methods: Over a 3-year period, a total of 46 patients were enrolled (mean age, 25.5 years; range, 18-33 years). Inclusion criteria consisted of symptomatic shoulder pain, limited range of overhead motion, inability to participate in overhead lifting activities, and examination findings consistent with scapular dysfunction secondary to a tight PM with tenderness to palpation of the PM tendon. All patients underwent a lengthy physical therapy and stretching program (mean, 11.4 months; range, 3-23 months), which was followed by serial examinations for resolution of symptoms and scapular tilt. Of the 46 patients, 6 (13%) were unable to adequately stretch the PM and underwent isolated mini-open PM release. Outcomes were assessed with scapula protraction measurements and pain scales as well as American Shoulder and Elbow Surgeons (ASES), Single Assessment Numeric Evaluation (SANE), and visual analog scale (VAS) scores. Results: Forty of the 46 patients (87%) resolved the tight PM and scapular-mediated symptoms with a dedicated therapy program (pre- and posttreatment mean outcome scores: 58 and 91 [ASES], 50 and 90 [SANE], 4.9 and 0.8 [VAS]; P < .01 for all), but 6 patients were considered nonresponders (mean score, 48 [ASES], 40 [SANE], 5.9 [VAS]) and elected to have surgical PM release, with improved scores in all domains (mean score, 89 [ASES], 90.4 [SANE], 0.9 [VAS]; P < .01) at final follow-up of 26 months (range, 25-30 months). Additionally, protraction of the scapula improved from 1.2 to 0.3 cm in a mean midline measurement from the chest wall preoperatively to postoperatively ( P < .01), similar to results in nonoperative responders. No surgical complications were reported, and all patients returned to full activities. Conclusion: In most patients, PM tightness can be successfully treated with a nonoperative focused PM stretching program. However, in refractory and pathologically tight PM cases, this series demonstrates predictable return to function with notable improvement in shoulder symptoms after surgical release of the PM. Additional research is necessary to evaluate the long-term efficacy of isolated PM treatment.